Image Enhancement Techniques for Digital Images - Ambresh Patel; Abhinav Shukla; Hemant Rajoriya (International Journal of Radio Frequency Innovations, 2025)
In image processing, image enhancement is a challenging problem. Image enhancement aims to process an image in a way that makes the final product better suited for a particular application than the original. There are numerous ways to improve the quality of images using digital image enhancement techniques. It is crucial to use these techniques correctly. Image enhancement is a critical aspect of image processing, focusing on improving the visual quality of an image to make it more suitable for specific applications. This is achieved through various techniques that enhance features such as contrast, sharpness, and detail, while reducing noise or blurring. The primary goal is to transform an image into a format that is better suited for interpretation, analysis, or presentation. The numerous methods frequently employed for image enhancement are compiled and examined in this document. Applications for image processing include image enhancement as a key component. Image enhancement has been the subject of a great deal of recent research. Numerous methods for enhancing digital photos have been put forth. The results of a study on different image enhancement methods are presented in this research work.
Keywords: CNN; Components; Digital image processing; Inferred image; image enhancement